OVERVIEW OF HEALTHCARE INNOVATION AND ENTREPRENEURSHIP - І. Геруш; В. Ходоровський; Т. Щудрова; О. Коротун; Т. Білоус (Bukovynian State Medical University, 2024)
The healthcare system is under constant pressure from a growing and aging population, escalating healthcare costs, limited resources and increasing demand. Achieving the triple aim of healthcare - improving care, improving health and reducing costs - requires innovation. According to the World Health Organization (WHO), health innovation is the development of new or improved health policies, systems, products and technologies, services and delivery methods that improve people's health, with a particular focus on the needs of vulnerable populations. Health innovations have both technological (innovative products, services or processes) and non-technological (organizational, policy, educational and social innovations) dimensions and play a critical role in improving the productivity, effi ciency, reliability, sustainability, safety and cost-eff ectiveness of health care. This article is the fi rst in a series of publications on innovation and entrepreneurship in health care. The paper examines the main types and categories of innovation and entrepreneurship, analyzes current innovation trends and directions in healthcare, factors that infl uence the adoption of innovative technologies in medical practice, and the characteristics of a human- centered approach to design thinking in healthcare. The article also discusses the concept of value- based healthcare, which focuses on providing the best possible care to achieve the best possible outcomes for each patient, using available resources effi ciently, and how innovation can improve the cost, quality, and access to healthcare.